Accuracy of lung ultrasound score in predicting the need for surfactant therapy in preterm neonates (less than 34 weeks) - Popat, Vedant Y.; Mehta, Ashish; Shah, Binoy; Gohil, Vishal; Shah, Manish; Thakkar, Dhiren; Patel, Maitray; Anant, Megha (International Journal of Contemporary Pediatrics, 2025)
Background: Lung ultrasound is a useful bedside tool in assessing different respiratory conditions of neonate. It is an emerging method in guiding clinicians to predict the need for surfactant administration in RDS neonates. Methods: This study included 75 neonates less than 34 weeks requiring any form of respiratory support. Lung ultrasound score (LUS) was done initially at birth followed at 6-12 hours of life. Surfactant administration was based on clinical assessment. Results: The LUS at birth (mean (SD): 8.5±2.93) and LUS at 6-12 hours of life (mean (SD): 6.2±3.06) showed a significant association with the requirement of surfactant administration and re-administration. Wilcoxon Sign rank test showed a significant decrease in the LUS score at 6-12 hours from LUS at birth. Also, the study shows that requirement of CPAP had positive correlation with LUS at birth and LUS at 6-12 hours. Conclusions: The study shows significant association of LUS at birth and requirement of surfactant administration. Also, there is correlation between LUS at birth and LUS at 6-12 hours helping in predicting need for repeat dose of surfactant.